Immunohistochemical expression of B-cell lymphoma 2 gene -Bcl-2 in endometrial carcinoma - Hozan Dler Dhahir; Jalal Ali Jalal; Zheen Othman Hama Faraj (Advanced Medical Journal)
Background and objectives: Apoptosis, a process of cell death, is inhibited by the B-cell lymphoma 2 protein, leading to the prolonged survival of cells. Participation of Bcl-2 in starting and advancement of endometrial carcinoma remains inconclusive, with varying results observed. The aims of this study were to assess the frequency of B-cell lymphoma 2 expression in endometrial carcinoma, and to investigate the connection between B-cell lymphoma 2 expression with some clinicopathological parameters.